(untitled) (Gestión y Gerencia, 2019)
The objective of the research was to identify the organizational practices for the accumulation of knowledge and the information management tools that foster their development in organizations. For this, a methodology was designed based on the systematic review and analysis of content, which would allow the relevant identification of knowledge accumulation practices and information management tools. Related to the organizational practices for the accumulation of knowledge, 79 practices were initially identified, which were consolidated into 17 for the internal creation of knowledge and 12 for the acquisition of external knowledge. About information management tools, 58 were initially identified, which were consolidated into 4 under the content approach and 14 under the technology focus as such. The investigation allowed to conclude that the capacity of accumulation of knowledge, understood as the internal creation of knowledge and the acquisition of external knowledge of organizations, is supported through its practices, techniques and information management tools that promote its construction and developmen